NEW STAGES OF LANGUAGE LEARNING THROUGH ONLINE PLATFORMS AND ARTIFICIAL INTELLIGENCE: NEW STAGES OF LANGUAGE LEARNING THROUGH ONLINE PLATFORMS AND ARTIFICIAL INTELLIGENCE - Dosmambetova, Muyassar (Журнал иностранных языков и лингвистики, 2025)
Language learning has always been an essential part of human development, facilitating communication and cultural exchange. In recent years, the integration of online platforms and artificial intelligence (AI) into language education has sparked a new era in the field. These technologies are reshaping the landscape of language acquisition by providing learners with tools that are more interactive, adaptive, and accessible. Online platforms offer a variety of resources, such as videos, interactive exercises, and collaborative spaces, which allow students to engage with the language in a more dynamic way. AI, on the other hand, can personalize the learning experience by adapting to the learner’s proficiency level, learning speed, and preferred teaching methods. This combination of online learning environments and AI-driven assistance is particularly relevant in countries like Uzbekistan, where the integration of technology into education is becoming a key focus for the government and educational institutions